2008
DOI: 10.1088/0268-1242/23/7/075049
|View full text |Cite
|
Sign up to set email alerts
|

6-T SRAM cell design with nanoscale double-gate SOI MOSFETs: impact of source/drain engineering and circuit topology

Abstract: 2008). 6-T SRAM cell design with nanoscale double-gate SOI MOSFETs: impact of source/drain engineering and circuit topology. Semiconductor Science and Technology, 23 (7), [075049]. https://doi. AbstractThe impact of source/drain engineering on the performance of a six-transistor (6-T) static random access memory (SRAM) cell, based on 22 nm double-gate (DG) SOI MOSFETs, has been analyzed using mixed-mode simulation, for three different circuit topologies for low voltage operation. The trade-offs associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Previous studies on underlap design in MOSFETs have shown significant improvement in digital and analog/RF metrics [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on underlap design in MOSFETs have shown significant improvement in digital and analog/RF metrics [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…24(b) shows a large cloud near the y axis at high WWTV and low values, corresponding to the values captured due to standby retention failures. The excellent agreement between extracted and large-scale read/write margin measurements suggest that read/write metrics measured using 11 The zero crossing of the WWTV measurements does not correspond to V = 0:6 V due to the application of a 100 mV WL weak write. direct bit-line characterization, which are easier to model than and can be fitted to simple Gaussian distributions, can be used to estimate .…”
Section: E Measurements 1) Distributions and Correlations With Read/mentioning
confidence: 90%
“…This effectively measures current minus current. The writeability current [10], [11], , is defined as the minimum measured current past the inverter trip point [ Fig. 1(e)].…”
Section: ) Writeability Currentmentioning
confidence: 99%
“…This effectively measures the current of the access transistor minus the current of the pull‐up transistor. The write‐ability current I W , 27 is defined as the least measured current past the trip point of the inverter Q. A bigger I W indicates a more writeable cell, whereas I W ≤ 0 indicates a write failure.From Figure 5D, we can see that the I W of our proposed HSLC12T cell is the largest of all the other compared radiation hardened cells, which is because in the write operation, the signal affects not only nodes Q and QN but also the other two nodes S0 and S1, facilitating the writing operation through feedback.…”
Section: Evaluation and Comparisonmentioning
confidence: 99%